2011
DOI: 10.1111/j.1475-3588.2011.00623.x
|View full text |Cite
|
Sign up to set email alerts
|

Review: A systematic review of the impact of physical activity programmes on social and emotional well‐being in at‐risk youth

Abstract: Background: Physical activity programmes have been identified as a potential strategy for improving social and emotional well-being in at-risk youth, who have a prevalence of depression and low self-esteem exceeding the general population. Methods: A systematic search of six electronic databases (EMBASE, OVID MEDLINE, PsychINFO, PubMed, Scopus and SPORTDiscus) was conducted to identify physical activity programmes designed to improve social and emotional well-being in at-risk youth. Results: The search identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
124
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(137 citation statements)
references
References 41 publications
5
124
1
7
Order By: Relevance
“…Although research indeed shows that sport participation by youngsters is associated with several beneficial outcomes such as social inclusion (Feinstein et al, 2005), academic achievement (Bailey, 2006), and social and emotional well-being (Eime, Young, Harvey, Charity, & Payne, 2013), no consensus has been reached on the evidence for a causal relationship. In addition, the mechanisms that explain how sport programmes positively affect life skills of socially vulnerable youth remain unclear (Lubans, Plotnikoff, & Lubans, 2012). Interestingly, the youth workers are only positive towards intersectoral action with local sports clubs if these pay attention to a positive socio-pedagogical climate and to the social skills of the coaches.…”
Section: Discussionmentioning
confidence: 99%
“…Although research indeed shows that sport participation by youngsters is associated with several beneficial outcomes such as social inclusion (Feinstein et al, 2005), academic achievement (Bailey, 2006), and social and emotional well-being (Eime, Young, Harvey, Charity, & Payne, 2013), no consensus has been reached on the evidence for a causal relationship. In addition, the mechanisms that explain how sport programmes positively affect life skills of socially vulnerable youth remain unclear (Lubans, Plotnikoff, & Lubans, 2012). Interestingly, the youth workers are only positive towards intersectoral action with local sports clubs if these pay attention to a positive socio-pedagogical climate and to the social skills of the coaches.…”
Section: Discussionmentioning
confidence: 99%
“…46 The development of self-regulation and coping skills promoted in recreational activities such as yoga and martial arts may explain the positive effects of these activities on mental health. 46,47 …”
Section: Behavioral Mechanismsmentioning
confidence: 99%
“…Besides these social and psychological mechanisms, physiological mechanisms are suggested for the relationship between sports participation and emotional and cognitive outcomes. For instance, it has been shown that physical activity leads to changes in neurotransmitters associated with improved well-being (Lubans, Plotnikoff, & Lubans, 2012), self-esteem (Cerin, 2010), and executive functioning (Diamonds & Lee, 2011). Finally, Bailey, Hillman, Arent, and Petitpas (2013) suggested that as many sports programs take place in a social setting, such programs provide youth with opportunities to develop social skills such as communication skills, conflict resolution, and empathy.…”
mentioning
confidence: 99%
“…Sports-for-development programs are sports programs intentionally structured to serve socially vulnerable youth's sports participation and/or life skill development (Coalter, 2015). Only Lubans et al (2012) systematically reviewed studies on the benefits of sports programs serving socially vulnerable youth. The authors provided an overview of quantitative studies published during 1990 to 2011 on the impact of outdoor activity programs, sports and skill-based programs, and physical fitness programs (e.g., aerobics and circuit training) on the social and emotional wellbeing of socially vulnerable children and youth aged 4 to 18 years old.…”
mentioning
confidence: 99%